Tunable multimodal adhesion of 3D, nanocrystalline CoFe2O4 pollen replicas. (6th November 2017) - Goodwin, W Brandon; Shin, Donglee; Sabo, Daniel; Hwang, Sunghwan; Zhang, Z John; Meredith, J Carson; Sandhage, Kenneth H
Abstract: 3D replicas of sunflower pollen microparticles, comprised of a multicomponent magnetic spinel ferrite (CoFe2 O4 ) with tailorable adhesive properties, have been synthesized for the first time via a conformal layer-by-layer (LbL) surface sol–gel (SSG) deposition process followed by organic pyrolysis and oxide compound formation at a peak temperature of 600 °C–900 °C. These high-fidelity ferrite pollen replicas exhibited multimodal (van der Waals, vdW, and magnetic) adhesion that could be tuned via control of the CoFe2 O4 nanoparticle and crystal sizes. The CoFe2 O4 pollen replicas exhibited a non-monotonic change in short-range ( 10 nm) vdW adhesion with an increase in the peak firing temperature, which was consistent with the counteracting effects of particle coarsening on the size and number of nanoparticles present on the sharp tips of the echini (spines) on the pollen replica surfaces. The longer-range (up to 1 mm) magnetic force of adhesion increased monotonically with an increase in firing temperature, which was consistent with the observed increases in the values of the saturation and remanent magnetization of CoFe2 O4 with an increase in average nanocrystal size. By adjusting the nanocrystal/nanoparticle sizes of the CoFe2 O4 pollen replicas, the total force of adhesion (vdW + magnetic) to a magnetic substrate could be increased by a factor of 3 relative to native pollen grains.